Perbaikan Sifat Tanah dan Peningktan Hasil Bawang Merah (Allium cepa grup Aggregatum) dengan Menggunakan Mulsa dan Bahan Pembenah Tanah - Haryati, Umi; Erfandi, Deddy (Jurnal Hortikultura Indonesia, 2019)
Soil in upland is degraded. Therefore it is necessary to improve the quality of the soil.  This researh aimed to determine the effect of mulch and soil amandment application on improving soil physical and chemical properties and its relation in increasing shallot yield. A Study of mulch and soil amandment application on shallot cultivation was conducted on Mar ch up to June during the 2016 planting season in Bayongbong Village, Bayongbong Subdistrict, Garut District, West Java Province. The experimental design was split plot design with three replications. The main plot were mulch type, they were whithout mulch (M-0), black plastic mulch (M-1), and straw mulch (M-2).  Meanwhile the sub plot were farmer practice, farmer practice plus NPK, farmer practice plus 5 t ha-1 dolomite, farmer practice plus 5 t ha-1 biochar and farmer practice + 5 t ha-1dolomite plus 5 t ha-1 biochar. The research results showed that mulch and soil amandement   improved physical soil properties, water retension, porosity, and soil aggregation.  In addition soil amendment improved soil chemical characteristics (pH, Ca2+, K+, Ca-exch., K-exch., base saturation).  There was an interaction between mulch and soil amendments on the shallot bulb yield. (18.35 t ha-1) was obtained by plastic mulch and farmer practice plus 5 t ha-1 dolomite that increased the yield up to 57.8 % than control, without mulch and farmer practice.Key words: plant growth, soil chemistry, soil physics, yield